Lost views and consolidated settlements: La Pueblica and Salto del Esla before and after the building of Ricobayo reservoir in Zamora - Fernández García, Noelia (Eikonocity. Storia e Iconografia delle Città e dei Siti Europei, 2021)
Ricobayo reservoir (1929-1935), built by the company Saltos del Duero in the Spanish province of Zamora, meant the devastation of villages like La Pueblica, but also the building of a new settlement, provisional at first and called Salto del Esla, which was consolidated as a village in the 1950s. It is aimed to recover the lost image of La Pueblica and to show the development of Salto del Esla, using diverse sources, such as photographs, audio visual material, postcards, and technical journals.